2016
DOI: 10.1111/bjh.14413
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of primary chemoresistance and remission induction failure in paediatric and adult acute myeloid leukaemia

Abstract: Cure rates of children and adults with acute myeloid leukaemia (AML) remain unsatisfactory partly due to chemotherapy resistance. We investigated the genetic basis of AML in 107 primary cases by sequencing 670 genes mutated in haematological malignancies. SETBP1, ASXL1 and RELN mutations were significantly associated with primary chemoresistance. We identified genomic alterations not previously described in AML, together with distinct genes that were significantly overexpressed in therapy-resistant AML. Define… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 15 publications
(18 reference statements)
5
36
0
Order By: Relevance
“…One possibility is that chemotherapy resistance is linked to transcriptional programmes that are either established in the cell of origin or acquired de novo during transformation, independently of specific somatic mutations. Consistent with this hypothesis, Brown et al (2016) identified several genes that were expressed more highly in diagnostic specimens from patients who failed induction as compared to those that achieved a remission. Similarly, Stavropoulou et al (2016) and Krivtsov et al (2013) have shown that KMT2A-MLLT3 (often termed MLL-AF9)-driven AMLs have distinct transcriptional programmes, distinct cytosine methylation profiles, more rapid growth and a poorer response to therapy when they arise from haematopoietic stem cells as compared to more differentiated granulocyte-monocyte progenitors.…”
supporting
confidence: 57%
See 4 more Smart Citations
“…One possibility is that chemotherapy resistance is linked to transcriptional programmes that are either established in the cell of origin or acquired de novo during transformation, independently of specific somatic mutations. Consistent with this hypothesis, Brown et al (2016) identified several genes that were expressed more highly in diagnostic specimens from patients who failed induction as compared to those that achieved a remission. Similarly, Stavropoulou et al (2016) and Krivtsov et al (2013) have shown that KMT2A-MLLT3 (often termed MLL-AF9)-driven AMLs have distinct transcriptional programmes, distinct cytosine methylation profiles, more rapid growth and a poorer response to therapy when they arise from haematopoietic stem cells as compared to more differentiated granulocyte-monocyte progenitors.…”
supporting
confidence: 57%
“…For example, RUNX1, DNMT3A and FLT3 mutations have been associated with inferior longterm survival (Ley et al, 2010;Schnittger et al, 2011;Patel et al, 2012), yet none of these mutations predicted induction failure in the study reported by Brown et al (2016). This suggests a disconnection between the mechanisms that cause induction failure (i.e.…”
mentioning
confidence: 83%
See 3 more Smart Citations